Student study guide [to] Computing in the information age - Forcht, Karen A. (John Wiley and Sons, 1996)
The basics of computing. From micros to Mammoths. Using productivity tools. Computer processing. Input and output. Secondary storage devices. Application packages. Developing custom software. Systems software. Connectivity, networks, and the information superhighway. Systems analysis and design. Database management information systems. Social issues in computing.